2020
DOI: 10.1097/jcn.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model of Rehabilitation Motivation in Middle-Aged Survivors of Stroke in Rehabilitation Facilities in Korea

Abstract: Background To improve the health outcomes of survivors of stroke, it is critical that they are highly motivated to engage in rehabilitation activities. Despite the increasing prevalence of strokes among middle-aged adults, there is limited knowledge regarding factors that may affect survivors' motivation to engage in rehabilitation. Objective The aim of this study was to examine the relationship among factors that predict the rehabilitation motivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…AAT has a significant positive effect on patients' general mood and wellbeing [18]. Post-stroke patients often have difficulty during rehabilitation due to negative emotions such as depression [6,7]. However, Theis et al (2020) showed that AAT triggers positive emotions and low levels of arousal in patients with acquired brain injury [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAT has a significant positive effect on patients' general mood and wellbeing [18]. Post-stroke patients often have difficulty during rehabilitation due to negative emotions such as depression [6,7]. However, Theis et al (2020) showed that AAT triggers positive emotions and low levels of arousal in patients with acquired brain injury [39].…”
Section: Discussionmentioning
confidence: 99%
“…The most typical psychological problem is depression, with a frequency of about 30% or more in patients post-stroke [4,5]. Depression has a negative effect on rehabilitation motivation, leading to missed rehabilitation periods and ongoing physical disabilities, as a result of which a vicious cycle of physical disorders is maintained [6,7]. According to previous studies, physical exercise has a positive effect on depression and rehabilitation motivation [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…5 Participants with post-stroke depression have less independence in activities of daily living and motivation for rehabilitation. [6][7][8] Furthermore, depression is associated with a worse functional outcome. 9 To date, PSD has typically been treated with pharmacological and psychotherapeutic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Among individuals with disabilities, self-evaluation related to the day-to-day management of their condition is of interest. Self-efficacy and self-esteem, which are psychological constructs influencing the management of stress and depression [ 5 , 6 ], can be conceived as components of core self-evaluations. These are fundamental assumptions an individual makes about themselves and their agency within their environment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%